Case report: Dupilumab-induced linear psoriasis: a rare presentation - Sun, Wen; Wang, Kexin; Ren, Yuekang; Yuan, Huajie; Lang, Xiaoqing; Guo, Shuping; Liu, Hongye (Frontiers in Medicine, 2025)
A 42 year-old male with prurigo nodularis treated with dupilumab showed a case of linear psoriasis, highlighting the potential of dupilumab to induce immune shift and chimeric gene expression.